2014
DOI: 10.5539/ibr.v7n4p125
|View full text |Cite
|
Sign up to set email alerts
|

CEO Compensation: Does Financial Crisis Matter?

Abstract: The topic of CEO compensation has been highly debatable. The financial crisis of 2008 further prompted public and media to question executive compensation practices in the United States. This study investigates the effect of the financial crisis on CEO compensation and also examines various determinants of CEO compensation. Using a sample of Fortune 500 firms and 2241 observations, we find that financial crisis has a small but significant effect on CEO compensation. Firm performance, firm size, and CEO duality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…As part of the analysis, we also assess the influence of board composition and the way these factors have been changing over time, particularly pre and post financial crisis. [30]. They, however, also found that while total compensation increased during and after the 2008 financial crisis, cash compensation decreased.…”
Section: Ceo Compensation and Mergers And Divestituresmentioning
confidence: 92%
“…As part of the analysis, we also assess the influence of board composition and the way these factors have been changing over time, particularly pre and post financial crisis. [30]. They, however, also found that while total compensation increased during and after the 2008 financial crisis, cash compensation decreased.…”
Section: Ceo Compensation and Mergers And Divestituresmentioning
confidence: 92%
“…For example, Ozkan (2011) studied a sample of 390 UK non-financial companies from 1999 to 2005 and found a pay-performance elasticity of 0.075 and 0.095 for CEO cash and total direct compensation (that is, for every 10% increase in shareholder wealth, CEO cash or total direct compensation increased 0.75% or 0.95%). Vemala et al (2014) studied the effect of the 2008 financial crisis on CEO compensation. Using a sample of 249 Fortune-500 firms and 2241 observations over the period from 2004 to 2012, firm performance was found to have a significant effect on CEO compensation both pre-and post-crisis.…”
Section: Theory and Research Evidence On Firm Size Performance Andmentioning
confidence: 99%
“…Furthermore, executive compensation levels and structure in Canada have changed significantly in the last 20 years because of, among other things, drastic changes in the economic environment (such as the dot-com bubble and the 2008 financial crisis), increasing social and shareholder pressure, and governance requirements (Chowdbury & Wang, 2009;Gélinas & Baillargeon, 2013;Vemala, Nguyen, Nguyen, & Kommasani, 2014). For example, during the five-year period covered by Zhou (2000), only about half of the CEOs received stock options and the use of stock options was considered as a pay-forperformance tool.…”
Section: Introductionmentioning
confidence: 99%
“…(number of shares outstanding x Closing Price) + DEBT According to research [15], [16] found that the higher the value of the company the greater the compensation of the CEO. [17], [18] revealed that firm value positively affects executive compensation.…”
Section: Company Valuementioning
confidence: 99%